Agricultural policy in developing countries - Hermann Priebe; Wilhelm Hankel (Intereconomics, 1981)
Development failures are less the result of “natural” short-comings, but are caused instead by false conceptions and by the misapplication of experience from highly-developed economic systems to countries in the initial development stage. The following article points out the pit-falls and discusses some alternative strategies.
Keywords: 330; Development Strategy